Aspartic proteases from basidiomycete Clitocybe nebularis - Sabotič, Jerica (Array, 2009)
Summary: We have isolated aspartic proteases by affinity chromatography from wild growing basidiomycete Clitocybe nebularis. Pepstatin A sensitive fractions from size exclusion chromatography were subjected to Concanavalin A affinity chromatography. N-terminal sequences of the three bands resolved on SDS-PAGE showed sequence similarity to the A01.018 group of family A1 aspartic proteases of the MEROPS classification. The diversity of putative aspartic proteases found in Clitocybe nebularis basidiocarp extracts is considerable and shows the great potential of basidiomycetes as a source of unique proteases that could find use in biotechnological applications and drug design